REAKSI PASAR TERHADAP PERISTIWA AKSI DEMO TANGGAL 22 MEI 2019 DI BURSA EFEK INDONESIA (BEI) - Maria P. L. Muga (Universitas Nusa Cendana, 2020)
ABSTRACT This study aims to examine the market reaction on the Indonesia Stock Exchange (IDX) for five days before and five days after the demonstration event on May 22, 2019. Market reaction is measured by the average abnormal return before and after the demonstration event on May 22, 2019. This is a listed company on the Indonesia Stock Exchange (IDX) whose shares are classified as LQ-45 share. The number of samples used was 34 companies. The hypothesis in this study was tested using Paired Samples Test analysis. The results of this test indicate that there is significant positive influence and significant differences before and after the demonstration event on May 22, 2019.Keywords :market reaction, abnormal return, demonstration event